Independent predisposing factors for subcutaneous and deep wound collection after total thyroidectomy: a prospective cohort study - Eweida, Ahmad; Ebeed, Hafsa Mohamed; Sakr, Mahmoud Fathy; Hamza, Yasser; Gabr, Essam; Koraitim, Tarek; Al-Wagih, Hatem Fawzy; Abo-Elwafa, Waleed; Abdel-Aziz, Tarek Ezzat; Nabawi, Ayman Sameh (Annals of medicine and surgery, 2018)
Background - The literature contains diverse and sometimes contradicting results about wound seroma following thyroidectomy. This is probably due to the subjective clinical estimation of seroma, or due to failure to differentiate between the occurrence of subcutaneous (SC) and deep wound collections. This work aimed at objectively investigating the factors affecting subcutaneous and deep wound seroma after thyroidectomy. - Methods - The relation between various operative and clinico-pathological factors and the collection formation was prospectively analyzed in a cohort of 100 patients after conventional thyroidectomy. Wound seroma was assessed clinically and via high-resolution ultrasonography at 24h, 48h and two weeks postoperatively. Sonographically detected collections were expressed as SC and/or deep wound collections according to the relation to strap muscles. - Results - Operative duration was the only independent factor significantly affecting the incidence of clinical seroma. Older patients (>40ys) showed significantly larger volumes of early SC collections. Early postoperative pain was significantly related to drain insertion, to the occurrence of clinical seroma and to the volume of SC collections. Sonographically, suction drains and shorter operative durations resulted in significantly less amount of deep collections. Suction drains did not result in less amount of SC collections or in a lower incidence of clinical seroma. - Conclusions - Operative duration is the only independent factor significantly related to clinically-detected postoperative seroma with its subsequent postoperative pain. Especially in elderly patients, a flapless technique would be recommended as these patients developed larger volumes of SC collections with subsequent higher pain scores, even if seroma was not clinically detected.
Gesehen am 07.04.2020